A Colorimetric/Fluorescent Dual Sensing System Based on the Enzyme-like Activity of Fluorescent Carbon Quantum Dots for Detection of Glucose - GUAN Huanan, ZHANG Mingyi, WANG Dandan, ZHANG Zhuzehui (Shipin Kexue)
A colorimetric/fluorescent dual-sensing assay for the detection of glucose was established based on the peroxidase-like activity of fluorescent carbon quantum dots derived from corncob. In the system, glucose oxidase was added to specifically catalyze the oxidation of glucose to produce H2O2, which was then reacted with 2,2’-azino-bis(3-ethylbenzothiazoline-6-sulfonic acid) under the catalysis of carbon quantum dots. Under optimized conditions, good linearity was observed between the absorbance (y) of the reaction system and glucose concentration (x) in the range of 0.001–0.5 mmol/L, which was fitted as follows: y = 10.907x + 0.659 5, R2 = 0.993 8, with a detection limit of 1.305 5 μmol/L. Moreover, good linearity was observed between the difference in fluorescence intensity (y) and glucose concentration (x) in the range of 0.001–0.1 mmol/L, which was fitted as follows: y = 9 172x + 4 438, R2 = 0.994 4, with a detection limit of 9.249 7 nmol/L. The method was applied to the detection of glucose in four real samples, with good spiked recovery rates and precision, which indicated that corncob fluorescent carbon quantum dots have the potential for application as an enzyme mimic in the detection of glucose.